Emotionally interactive agents - Iza-Miqueleiz, Mauricio (My University, 2018)
Models in language processing have researched how words are interpreted by humans. Many models presume the ability to correctly interpret the beliefs, motives and intentions underlying words. The interest relies also on how emotion motivates certain words or actions, inferences, and communicates information about mental state. As we will see below, some tutoring systems have explored this potential to inform user models. Likewise, dialogue systems, mixed-initiative planning systems, or systems that learn from observation could also benefit from such an approach. As these experimental data show, activating accessible constructs or attitudes through one set of stimuli can facilitate cognitive processing of other stimuli under certain circumstances, and can interfere with it under other circumstances. Some of the results support and converge on those centered on the constructs of current concern and emotional arousal. Future research has to take seriously into account this question: how to develop models where emotion interacts with cognitive processing. One example could be the work of Pitterman et al. (2010) where it is combined speech-based emotion recognition with adaptive human-computer modeling. With the robust recognition of emotions from speech signals as their goal, the authors analyze the effectiveness of using a plain emotion recognizer, a speech-emotion recognizer combining speech and emotion recognition, and multiple speech-emotion recognizers at the same time. The semi-stochastic dialogue model employed relates user emotion management to the corresponding dialogue interaction history and allows the device to adapt itself to the context, including altering the stylistic realization of its speech.
Keywords: Emotional processing; Emotional agents